FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA - Hartanti, Indiana Bella; Setiawanta, Yulita (Politeknik Negeri Ambon, 2025)
Introduction: The sluggish exports have led to tax avoidance in the basic and chemical industries, declining orders, and an abundance of domestically produced products, thus putting pressure on this sector. This study aims to investigate the effects of Audit Committee, Leverage, Return on Asset, and Company Size on Tax Avoidance and test them empirically. Methods: This study will apply a quantitative method with a research sample in the form of secondary data in the form of annual reports of companies engaged in the basic industry and chemical industry groups that are continuously listed on the Indonesia Stock Exchange during 2019 to 2023. The purposive sampling method is applied in this research and produces 85 data. The analysis was carried out using the SPSS 29.0 analysis tool to answer the research hypothesis with the multiple linear regression analysis method. Result: The findings show that CETR can be affected by ROA and SIZE while AC and DER are not. Further research can include other variables, expected to determine the antecedents that are able to predict tax avoidance. Further research can introduce more factors, such as liquidity, firm value, sales growth, transfer pricing, utilization of tax havens, tax rates or earnings management, which can describe tax avoidance. In addition, this research only presents the population in basic and chemical industry sector companies, further research is expected to take other sectors outside the research or take the entire series of manufacturing companies to enlarge the number of samples and observations to develop the research. Keyword: Audit Committee, Leverage, Return on Asset, Company Size, Tax Avoidance